Social immune response reflects infection progression in a soldierless termite - da Silva, Luiza Helena Bueno; Goes, Aryel C. [UNESP]; Rodrigues, Andre [UNESP]; Fourcassié, Vincent; McMahon, Dino; Haifig, Ives (Springer Nature, 2025)
Social interactions represent a double-edged sword. On one hand, sociality can facilitate sanitary collective behaviours; on the other hand, it creates opportunities for pathogen transmission. In termites, sanitary behaviours can entail a rescuing strategy at early stages of infection, followed by the elimination at later stages. We explored whether the neotropical soldierless species Anoplotermes pacificus employs a progressive approach towards infected nestmates, with different behavioural displays depending on the infection stage. We infected A. pacificus workers with the fungus Metarhizium anisopliae and incubated them for 2, 12, 15 and 20 h, corresponding to infection progression and, therefore, severity. Infected termites were placed with naïve nestmates and their behaviours were recorded for 3 h. Fungus-infected termites triggered up to fourfold higher levels of sanitary behaviour than in non-infected termites. Antennation behaviour decreased during the observation period, whereas sanitary behaviour, which we defined as directed behaviour towards the focal termite involving mouthparts, increased in frequency as incubation duration increased. Sanitary behaviour therefore appears to be a strategy for colony disinfection, which varies in intensity according to infection status, ultimately resulting in the immobilisation of infected individuals at later stages of infection. Alarm responses were also up to three times more frequent in treatment than in control groups and did not vary with incubation duration. A. pacificus workers therefore identify, communicate and respond to pathogen-treated individuals in a progressive manner, indicating that collective responses in this species are also significantly shaped by the stage of infection. By progressively modulating their social immune responses, termites may be able to optimize resource allocation within the colony by balancing the risk of individual infection versus protection of the group.
Keywords: Anoplotermes pacificus; Hygienic behaviours; Infection; Isoptera; Metarhizium; Social immunity